2006
DOI: 10.1111/j.1365-2133.1973.tb02948.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of HL-A antigens in dermatitis herpetiformis

Abstract: SUMMARY In dermatitis herpetiformis (DH) there are small intestinal abnormalities similar to those in adult coeliac disease (ACD) and there is evidence of other similarities between the two conditions, including immunological disturbances. Two reports of patients with ACD have shown a distinctive distribution of HL‐A phenotypes, with a high incidence of HL‐Ai and 8. A recent paper has described an increased incidence of HL‐A8 in DH. We report a similar study of patients with DH. Twenty‐one of thirty‐five patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The frequencies of HLA-B8 and phenotype Al-B8 found in this study were comparable with those reported previously in the Scottish population (White et al 1973, Da Costa et al 1974.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The frequencies of HLA-B8 and phenotype Al-B8 found in this study were comparable with those reported previously in the Scottish population (White et al 1973, Da Costa et al 1974.…”
Section: Discussionsupporting
confidence: 91%
“…This study is of particular interest since Scotland, which almost equals Finland's highest mortality rate anywhere from IHD in young men (W.H.O. 19721, also has a high frequency of HLA-B8 and A1-B8 in the population (White et al 1973, Da Costa et al 1974.…”
mentioning
confidence: 99%
“…The frequency of HLA-B8* (HL-A8) has been reported to be increased in dermatitis herpetiformis (DH) (Katz et al 1972, White et al 1973) and coeliac disease (CD) (Falchuk et al 1972, Stokes et al 1972). An increased frequency of an MLC-activating determinant in coeliac disease has also been indicated (Solheim et al 1974).…”
mentioning
confidence: 99%
“…1972 j White, et al, 1972) but also in thyroid disease (Grumet et al, 1973). This could be a cormecting link and whilst it might be interpreted as evidence of the (auto)-immunological nature of the two diseases it could equally well be an indication of a genetically determined disordered iodine metabolism.…”
mentioning
confidence: 99%